Multi-Dimensional Modeling of the Influence of Cell Design on Temperature, Displacement and Stress Inhomogeneity in Large-Format Lithium-Ion Cells. Issue 14 (1st January 2016) - Rieger, Bernhard; Erhard, Simon V.; Kosch, Stefan; Venator, Moritz; Rheinfeld, Alexander; Jossen, Andreas
Abstract : In this paper, an efficient multi-dimensional approach to model mechanical effects in lithium-ion cells is presented. Using this modeling approach, we introduce mechanical criteria to rate different cell designs, complementary to commonly used criteria such as homogeneity of temperature or current density distribution. The additionally considered mechanical criteria are the displacement distribution on the cell due to the superposition of intercalation induced volume changes and thermal expansion, and the stresses in the electrodes' active material particles. Two cell designs are compared comprising identical electrode stack dimensions with differing tab alignments. The model shows that the variation in local cell displacement is small due to the overlay of thermal and intercalation displacement, which act in opposite directions during discharge. Looking into the stress formation in the active material particles, we found that the tab pattern can influence the maximum stress and the gradients in stress distribution significantly, especially for the positive electrode particles. Our study shows the interaction of the electrochemical, electrical, thermal, and mechanical behavior of large-format pouch cells, representing a step toward a better understanding of the complex processes in lithium-ion cells and enabling the multi-disciplinary design optimization considering mechanical effects in an early stage of cell development.